A bio-inspired climb and glide energy utilization strategy for undersea vehicle transit. (1st February 2018) - Miller, Timothy F.
Abstract: Marine animals have been the bio-inspirational source for some novel concepts for locomotion, sensing, and the intelligent control of undersea vehicles. There has been little (if any) research in the area of bio-inspired energy utilization strategies applied to undersea vehicles. For example, there are reasons why some fish swim at a specific cruise speed; why some fish move by burst acceleration to higher speeds followed by coasting; and why some negatively buoyant fish alternately glide downwards, and then swim upward. The goal of this study is to develop the theory and models of the climb and glide form of autonomous undersea vehicle transit in a form that can permit assessment of future practical technology insertions (such as drag reduction and wing design). In addition, existing theory was expanded to address vehicles with significant wet weight and the effect of hotel load (equivalent to the basal metabolic rate of animals). Several observations from this preliminary analysis for climb/glide operation of practical vehicles were made. Over a practical and useful range of hotel loads and net vehicle lift-to-drag ratios, energy savings benefits relative to level flight transit from 10% to excess of 40% can be expected. This translates directly into a 10–40% increase in range if a climb/glide strategy is employed instead of level flight transit under the right operating conditions. Highlights: The mathematical theory of transit of negatively buoyant autonomous undersea vehicles is developed. The transit concept is bio-inspired and employs powered ascent followed by powerless glide. Transit with this mode can provide energy savings in excess of 40%.